69 Automated TRB locus haplotype analysis by long-amplicon TCRB chain sequencing for potential immune-related adverse events biomarker research. (9th November 2020) - Burke, Jennifer; Chen, Frances; Huang, Jiajie; Lowman, Geoffrey; Looney, Timothy; Sedova, Marina
Abstract : Background: Identifying potential predictive biomarkers for immune related adverse events (irAEs) following checkpoint blockade inhibition (CPI) remains an outstanding goal of immune-oncology translational research. Polymorphism with the T cell receptor variable gene (TRBV) has been proposed as a potential risk factor for irAEs owing to a potential link between TRBV polymorphism and chronic autoimmune disease. Efforts to interrogate the potential biomarker utility of TRBV polymorphism have been hampered by the repetitive nature of the TRB locus. Our research has demonstrated a method for inferring TRB locus haplotypes from long-amplicon TCRB chain sequencing data, which we used to identify major haplotype groups in from nucleic acid. Here we present our research for a potential automated method for haplotype group assignment from TCRB chain sequencing data. Methods: Rearranged TCRB chains from 10 blood samples were amplified and sequenced from 25ng peripheral blood total RNA via the Oncomine™ TCRB-LR assay using the Genexus™ Integrated Sequencer. 12 samples were run per chip with 4 samples run in each lane. TCRB clonotyping and repertoire feature analysis was performed using Genexus™ analysis software. Automated haplotype group assignment was performed by generation and comparison of TRBV allele profiles to those presented previously. 1 For context, TCR evenness, convergence, and haplotype group assignment were compared to values obtained following analysis of the same samples via the GeneStudio™ S5 platform and Ion Reporter™ 5.12 software. Results: TCR Evenness and convergence values were highly correlated across replicates run on the Genexus™ Integrated Sequencer (Spearman correlation >0.95 and >0.70, respectively). Evenness at equivalent clone count and convergence at equivalent sequencing depth were not significantly different across platforms (Spearman correlation >0.88). Haplotype group assignments demonstrated 100% agreement across replicates on both platforms. Conclusions: Our research has demonstrated a potential automated and reproducible method for TRB haplotype group assignment via the Oncomine™ TCR-Beta LR Assay, GX run on the Genexus™ Integrated Sequencer. Future studies will be needed to evaluate the potential biomarker utility of TRB haplotyping for the prediction of irAEs.For research use only not for diagnostic procedures. Reference: Looney T, Duose D, Lowman G, Linch E, Hajjar J, Topacio-Hall D, Xu M, Zheng J, Alshawa A, Tapia C, Stephen B, Wang L, Meric-Bernstam F, Miller L, Glavin A, Lin L, Gong J, Conroy J, Morrison C, Hyland F, Naing A. Haplotype Analysis of the T-Cell Receptor Beta (TCRB) Locus by Long-amplicon TCRB Repertoire Sequencing. J Immunother Precis Oncol 2019;2:137–143.